Change of avalanching parameters in the near zone of explosion site - E. G. Mokrov; N. V. Barashev (Лëд и снег)
Spatial variations of avalanche formation parameters in the relation with the explosive mass and its location have been experimentally studied. The charges were installed in five locations: on the ground, in the snow layer at a height of 0.6 m above the ground, on the snow surface, at a height of 1 m and 2 m above the snow surface. Mass of explosive was 0.5, 1, 2 and 4 kg. The experiments were in March 2012 on the Suoluayv plateau (600 m a.s.l.) in Khibiny Mountains. Studies have shown that at explosion sites the disturbance of snow structure, its density and shear strength occurs throughout the whole depth of snow cover, depending on the structure and density of snow layers as well as the explosive mass and its location.